KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN ORGANISASI PEMBELAJAR (LEARNING ORGANISATION) DI MADRASAH ALIYAH NEGERI KABUPATEN KUBU RAYA - Setyopratiwi, Tanti Utami; Wahyudi, H.; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this study to obtain information about the headmaster's leadership in developing a learning organization (learning organization) in Madrasah Aliyah Kubu Raya district. While the technique of checking the validity of the data is that researchers use triangulation and member checks. The results of this study can be concluded: 1) head of the madrasa develop learning organization in District, among others: able to understand the duties, functions and responsibilities as a teacher. The principal way affects teachers and staff, among others: charisma, authority and friendly and have properties such as honest, assertive, disciplined, thoughtful and confident, the way the principal directs teachers and staff, among others: to involve teachers in training or training, coaching teaching organization, the principal way to motivate teachers and staff, among others: the physical environment of the school setting, the setting suasan work, discipline, respect and Learning Resources development (PSB) and the way teachers and principals to guide staff with supervision and 2) Achievement of organizational development results learners in Madrasah Aliyah Kubu Raya District, among others: many accomplishments earned both academic and non-academic and the establishment of infrastructure building and presentatif well-ordered, thereby increasing the motivation of students who go to MAN Kubu Raya from different regions around the Kubu Raya from different regions around the Rasau Jaya which annually increases and is transformed into a state of 27 madrasas in Kubu Raya. Keywords: Principal Leadership, Learning Organization Abstrak: Tujuan penelitian ini untuk memperoleh informasi tentang kepemimpinan kepala madrasah dalam mengembangkan organisasi pembelajar (learning organization) di Madrasah Aliyah Negeri Kabupaten Kubu Raya. Hasil penelitian ini menunjukkan: Kepala madrasah mengembangkan organisasi pembelajar, antara lain: mampu memahami tugas, fungsi dan tanggungjawabnya sebagai guru. Cara kepala madrasah mempengaruhi guru dan staf antara lain: berkarismatik, penuh wibawa, ramah dan memiliki sifat seperti jujur, tegas, disiplin, bijaksana dan percaya diri, cara kepala madrasah mengarahkan guru dan staf antara lain: mengikut sertakan guru dalam pelatihan atau diklat, pembinaan organisasi pengajaran, cara kepala madrasah memotivasi guru dan staf antara lain: pengaturan lingkungan fisik madrasah, pengaturan suasana kerja, disiplin, penghargaan dan Pengembangan Sumber Belajar (PSB) dan cara kepala madrasah membimbing guru dan staf dengan melakukan supervisi dan pencapaian hasil pengembangan organisasi pembelajar, antara lain: banyaknya prestasi yang diperoleh baik bidang akademik maupun non akademik, dengan terbangunnya sarana dan prasarana gedung yang tertata baik dan refresentatif, sehingga menambah motivasi siswa yang masuk ke MAN Kubu Raya dari berbagai daerah di sekitar Rasau Jaya yang setiap tahunnya meningkat dan MAN Kubu Raya merupakan Madrasah Aliyah yang dinegerikan dari 27 madrasah yang ada di Kubu Raya. Kata Kunci: Kepemimpinan Kepala madrasah, Organisasi Pembelajar